2022
DOI: 10.1101/2022.05.03.490467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mass photometric detection and quantification of nanoscale α-synuclein phase separation

Abstract: α-Synuclein (α-Syn) liquid-liquid phase separation (LLPS) leads to irreversible amyloid fibril formation associated with Parkinsons disease pathogenesis. Critical concentrations of α-Syn LLPS are relatively high under physiological solution conditions. Moreover, α-Syn exhibits delayed LLPS kinetics under certain conditions which deviates from the behaviour predicted by classical homogeneous nucleation theory. In the current body of work, using interferometric light scattering (iSCAT), also known as mass photom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 100 publications
3
26
0
Order By: Relevance
“…Similar phase diagram of ASN mixed with PEG8000 was also observed by Sawner's group 11 and Ray's lab. 22 ASN selfassemblies, without applying a crowding agent, were also observed after 24 hours of incubation (the first column of ESI † Fig. S2).…”
Section: Resultsmentioning
confidence: 97%
“…Similar phase diagram of ASN mixed with PEG8000 was also observed by Sawner's group 11 and Ray's lab. 22 ASN selfassemblies, without applying a crowding agent, were also observed after 24 hours of incubation (the first column of ESI † Fig. S2).…”
Section: Resultsmentioning
confidence: 97%
“…In vitro α-Syn droplets were generated in the presence of crowding agents or high salt concentration through LLPS and the protein was shown to acquire solid-like properties in a time-dependent manner (27)(28)(29)(30)(31). Besides, some data suggest that α-Syn can form nanoscale structures below the saturation concentration, playing a role in aggregation (32). These in vitro observations did not take into account complex biochemical phenomena that take place within cells such as promiscuous interactions, crowding within the cytosol, cellular compartmentalization, and stress (33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, recent experiments revealed that nanoscale condensates comprised of various protein species can remain stable in pure aqueous solutions without coarsening [14, 20-24]. In these cases, the above mentioned mechanisms do not apply, yet the conventional coarsening theories, namely BMC and Ostwald ripening, also fail to explain the suppressed coarsening dynamics [25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that nanoscale condensates in cells have functional implications in a variety of biological contexts [7, 27], including postsynaptic density in neurotransmission [28], transcriptional condensates in gene transcription [26, 29, 30], and heterochromatin in chromatin compaction [31, 32]. Investigating the temporal evolution of nanoscale condensates is therefore particularly critical for unraveling the intriguingly slow coarsening behaviors, despite technical challenges that nanoscale condensates are typically beyond the detection limit of conventional experimental techniques, such as fluorescence microscope and UV-vis spectroscopy [7, 20].…”
Section: Introductionmentioning
confidence: 99%